Free India in Asia - Levi, Werner (Minneapolis, 1952)
The importance of India in world affairs is reflected in the nu merous books and articles written on Indian foreign policy within recent years. Most of them are in a speculative and argumentative vein, either defending Indian policy or, more often, attacking it. The basis of these attacks is sometimes partisan fury, sometimes disappointment. Partisan fury, because the Indian government has succeeded so far in keeping the country out of the two camps fight ing the Cold War. Disappointment, because the Indian govern ment or Nehru personnally has been unable to pursue a policy after independence which squares fully with the high ideals and principles in whose name the battle for freedom was fought. The unfortunate fact is that no government and no statesman can ever in a world of nation-states pursue a foreign policy which puts morals first and the national interest-whose core is understood to be national security-second. Compromises on national or personal ideals are inevitable as long as the nation-state system persists. If statesmen betray ideals for what they honestly consider the national interest, one may criticize their concept of the national interest or the system which makes betrayal necessary, but one can hardly criticize the betrayal.
Keywords: International Relations